The Effect of Using Different Types of Tasks on the tenth Grade Students' Reading Comprehension Achievement - Permatasari, Diayu Galuh; Bindarti, Wiwiek Eko; Tasnim, Zakiyah (English Education Study Program, 2016)
This research was aimed to know the effect of using different types of tasks on students' reading comprehension achievement. The research design of wasa quasi-experimental with non-equivalent group post-test-only design. Clusterrandom sampling was used to determine the respondents of the research. . Theresearch area was at MA Al-Qodiri Jember. The research respondents were thetenth grade students chosen as the experimental and the control groups by lottery.The data of this research were obtained by doing interview, documentation and test.The research data were analyzed by using t-test. The result of t-test showed thatthere was a significant mean score difference between the two classes. Therefore,using different types of tasks gave a significant effect on the eighth grade students'reading comprehension achievement at MA. Al-Qodiri Jember.